Bowling Number’s Game as an Effort to Improve Children’s Ability to Recognize Number Symbol - Rahmalia, Renny (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The aims of this study is to determine the ability to recognize number symbols in children aged 4-5 years at Darussakam Petapahan Jaya Kindergarten before and after using the Bowling game. The method used in this research was Pre-Experimental with a One-Group Pretest-Posttest Design. This design used a pre-test at the beginning before the research as a way to find out children's ability to recognize the concept of numbers in children before being given treatment. Then, further treatment was carried out or given to research subjects using the Number Bowling Game. A post-test was carried out to obtain data on the ability to recognize the concept of numbers after being given treatment. Based on the analysis of the Wilcoxon signed Rink Test, which at the time of the Pre-test showed the results of 9 children, there were 6 people (60%) could recognize number forms were in the undeveloped range and 3 people (40%) started to develop. After Post-test of the Bowling game, 9 of the children were in very well-developed criteria (BSB). Statistical Test show that Asymp.sig (2-tiled) 0.007 < 0.05. This means that there is an influence of bowling games on the ability to recognize the shape of the number symbol in children Keyword: Bowling Games. Symbol of Numbers, Early Childhood 4-5 year olds.